Terpyridine-Containing π-Conjugated Polymers for Light-Emitting and Photovoltaic Materials - Liu, Pan; Shi, Ganhui; Chen, Xuegang (Frontiers in Chemistry, 2020)
2,2′:6′,2″-Terpyridine (tpy) is a versatile moiety used in the construction of small novel molecules or polymers. Extending or coupling tpy with π-conjugation structures can result in interesting optoelectronic properties. This mini-review summarizes the significant progress made over the past decades in the study of tpy-containing π-conjugated polymers and their application in light-emitting and photovoltaic materials. When coordinated with metal ions, tpy exhibits immense potential for the synthesis of metallo-supramolecular or metallo-polymer materials. Therefore, tpy-based metallo-polymers are the primary focus of this study. Selected examples will be reviewed with a special emphasis on the properties of these functional systems, which can consequently help further their application in light-to-electricity or electricity-to-light conversion fields.